Composition and Structure of Tree Species in the Main Campus of Usmanu Danfodiyo University, Sokoto, Nigeria: Composition and Structure of Tree Species (South Asian Journal of Agriculture, 2025)
The number of anthropogenic activities on the university's main campus has increased recently. Trees are constantly being felled for the erection of different structures to accommodate the growing number of employees and students leading to the alteration of the diversity, composition and structure of the tree species within the main campus. This study was therefore carried out to investigate the current diversity, composition, and structural characteristics of the tree species within the study area. Aerial photographs were used to categorize the areas with similar tree arrangements in to clusters- Shelterbelts (SH), Avenue Trees (AT), Academic Areas (AA), and Fadama Areas (FA). Thirteen (13) sub-clusters (sampling units) were selected out of 25. Fifty percent (50%) of each of the selected sub-clusters were randomly selected for data collection. Line transects (200m) were laid and data along every first 20m of each transect was collected for sampling units with linear arrangement and this was repeated after every 200m interval while for sub-clusters with scattered arrangements, variable circular plots were used. Shannon-Weiner Index (Ὴ) was also estimated. A total of 566 trees belonging to 15 species, 13 genera, and 10 families were identified and their diameter at breast height (DBH) were measured, recorded and analyzed using descriptive statistics.  The result showed that Azadirachta indica was the most abundant tree species in the study area with 55.12% particularly in SH, AT and AA. The study also reveals the variations in mean DBH among tree species with Faidherbia albida having the highest mean DBH of 0.963m, indicating substantial individual tree sizes. The study also revealed that while Azadirachta indica dominated in most clusters, Mangifera indica stood out in the FA. Shannon-Weiner Index (Ὴ) value of 1.491 was obtained. Signifying a low diversity in the study area. The highest IVI was recorded in A. indica 96.16% and the least was recorded in P. guajava 0.83%. The findings suggest intensified reforestation efforts, establishment of new plantations, and incorporation of economically beneficial plants such as Cashew (Anacardium Occidentale) for enhanced biodiversity and economic benefits within the university community as recommendations.South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 46-61